Analisis Tingkat Kebisingan Di Jalan Ahmad Yani Palangka Raya: Analysis Of Noise Level On Ahmad Yani Street Palangka Raya - Devia Devia (Media Ilmiah Teknik Sipil, 2023)
In region that social activity, economy, and the culture increase can cause environmental noise, the noise occurs because traffic flow activity. The traffic noise is total from noise that raised from each vehicle in traffic flow. This research level of noise on Ahmad Yani Street is at office area, store are and traditional market, therefordo needs to be conducted in order to determine the noise levelon the area and to compare it with noise level stamdard which refers to regulation Ministry Of Environment. This research  consist of four time intervals by using Sound Level Meter. Data processing to determine the noise level and compare noise level standard. From the research conducted that the noise level occurs between 73,64 dBA – 74,51 dBA. The highest noise level is between 09.00 – 11.00 WIB that is 74,51 dBA. The result for the noise level of 16 hours during the day are 72,60 dBA. That is on Ahmad Yani Street exceeds the noise level quality standard by KEP.48/MENLH/1996 for office area and trade area are 50 – 65 dBA